U.S.-Vatican relations, 1975-1980 : a diplomatic study - Sarros, P. Peter (ADST-DACOR diplomats and diplomacy series., 2020)
"This book explores the bilateral relations between the United States and the Vatican from 1975 to 1980, a turbulent period that had two presidents, three presidential envoys, and three popes. This previously untold story shows how the United States and the Vatican worked quietly together behind the scenes to influence the international response to major issues of the day. Peter Sarros examines the Iran hostage crisis, the tensions of the Cold War, the Helsinki process, and the Beagle Channel dispute, among other issues. These interactions produced a tacit alliance in the foreign policies of the United States and the Vatican even before the establishment of full diplomatic relations. This unique book is based largely on official documents from the archives of the Office of the U.S. Special Envoy of the United States to the Vatican, supplemented by Sarros's contemporaneous diaries, notes, and other unpublished sources. The confidential consultations at the Vatican by three special envoys and by Sarros in his role as charge and ambassador at the Vatican were critical in obtaining Vatican support on major international issues. The Vatican also derived substantial benefits from the partnership through U.S. support of Vatican initiatives in Lebanon and elsewhere, and by U.S. policies that gave Vatican diplomacy the flexibility to play a larger role in the international sphere. Sarros concludes that American diplomacy was successful at the Holy See during this period because it took advantage of the Vatican's overarching international strategy, which was to increase its influence through support for the global balance of power while blocking the expansion of Soviet power and communism in Europe. U.S.-Vatican Relations, 1975-1980 will be of interest to students and scholars of history and political science, especially in the fields of diplomatic relations and church history"--